Determination of Association Constants of b-Cyclodextrin and b-Cyclodextrin-N-succinamate with Drugs by High Performance Liquid Chromatography - Ashnagar, Alamdar; J. Easton, Christopher; Gharib Naseri, Nahid (Asian Journal of Chemistry, 2016)
Investigation of the Hummel and Dreyer method for the estimation of stability constants by high performance liquid chromatography (HPLC) is described. Comparison of the results obtained for binding of cimetidine (2a) and 2-(p-tolyl)ethylamine (2b) to b-cyclodextrin (1a) and b-Cyclodextrin-N-succinamate (1b) by 1H NMR (300 MHz) spectroscopy and the HPLC method were studied. The results indicated that the stability constants by HPLC method are higher and more accurate, and are 431 and 470 dm3 mol-1 for (2a) and 138 and 111 dm3 mol-1 for (2b) in binding to (1a) and (1b), respectively.